Search for resonant Higgs boson pair production in the semi-leptonic bb ̅WW* decay channel with the ATLAS detector at the Large Hadron Collider - Bin Norjoharuddeen, N (2018)
This thesis presents the search for resonant Higgs boson pair production with the bbWW* decay mode in the semi-leptonic final state containing one electron or muon with multiple jets and missing transverse momentum. The Standard Model of particle physics predicts only non-resonant pair production of Higgs bosons but a number of theoretical models predict massive new particles that decay to two Higgs bosons. The search is performed using ps = 13 TeV proton-proton collision data collected in 2015 and 2016, corresponding to an integrated luminosity of 36:1 fb-1, recorded by the ATLAS detector at the Large Hadron Collider. The search focuses on TeV-scale resonances which decay to two Higgs bosons with large transverse momenta. Jets with large radius parameter are used to reconstruct the kinematics of one of the Higgs bosons which decays hadronically into a pair of b-jets. The invariant mass of the reconstructed Higgs boson pair is used to test the compatibility of the observed data with the Standard Model background prediction. No statistically significant excess is observed in data over the expected Standard Model background and upper limits are placed with 95% confidence level on the resonant Higgs boson pair production cross section times branching ratio for narrow spin-0 and wide spin-2 resonant states. Techniques which use advanced subjet reconstruction algorithms to improve identification of high momentum Higgs boson decays to b-jets are also presented. The three algorithms demonstrate significant performance improvements in simulation compared to the standard method currently used by the ATLAS collaboration.